2015
DOI: 10.1111/exd.12624
|View full text |Cite
|
Sign up to set email alerts
|

Novel KRT83 and KRT86 mutations associated with monilethrix

Abstract: This study is unique in bringing together 12 affected individuals in three pedigrees one of which consisted of five generations. The affected individuals were all from three isolated villages within each other's vicinity (approximately 20-30 km distance from each other). Repeated use of common names in the different villages prompted us to consider the possibility that the population of different villages shared a common ancestor. Clinical findings in heterozygous carriersWhile documenting clinical features an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
3
21
1
Order By: Relevance
“…In contrast, heterozygous missense variants of KRT83 , c.1219G>A (p.Glu407Lys) and c.1252G>A (p.Glu418Lys), have been reported in two families with the autosomal dominant hair disorder, monilethrix (MIM 158000) 18 19. In the family segregating the p.Glu407Lys substitution, one of the three affected members additionally exhibited mild follicular hyperkeratosis.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, heterozygous missense variants of KRT83 , c.1219G>A (p.Glu407Lys) and c.1252G>A (p.Glu418Lys), have been reported in two families with the autosomal dominant hair disorder, monilethrix (MIM 158000) 18 19. In the family segregating the p.Glu407Lys substitution, one of the three affected members additionally exhibited mild follicular hyperkeratosis.…”
Section: Discussionmentioning
confidence: 97%
“…It is of special interest to note that we had the opportunity in the past to check the Venezuelan patients IV‐1 and IV‐2 reported in van Steensel et al. 's paper , who were not available for this study, and found the same mutation (c.1226T>C in KRT86 ) in these two sisters as well as in their father (Fig. S1).…”
mentioning
confidence: 92%
“…Importance of keratins for hair shaft integrity and curvature. Mutations in keratins expressed in the distal part of the hair cortex, such as K81, K83 and K86, lead to moniltherix, which is characterized by fragile hair . This points to the fact that the hair cortex is mostly important for giving the strength to the hair shaft.…”
mentioning
confidence: 99%
“…However, they can and do reflect the life lived—as the fibre becomes a repository for various chemical moieties that result from cellular metabolism, pollution and metabolites of drugs as they pass from blood to cells in the follicle and remain sequestered in the hair fibre. Fibre morphology can also tell a story of hair damage and more rarely, genetics, as recently described by van Steensel et al . who discovered polymorphisms in two hair keratin genes KRT83 and KRT86 in monilethrix.…”
mentioning
confidence: 95%
“…However, they can and do reflect the life livedas the fibre becomes a repository for various chemical moieties that result from cellular metabolism, pollution and metabolites of drugs as they pass from blood to cells in the follicle and remain sequestered in the hair fibre. Fibre morphology can also tell a story of hair damage and more rarely, genetics, as recently described by van Steensel et al8 who discovered polymorphisms in two hair keratin genes KRT83 and KRT86 in monilethrix. However, in cosmetic science, the relationship of fibre Commentary | 551 morphology to function/behaviour is often a very subtle one, requiring ever more sophisticated methods for differentiating products and their benefits for the consumer.Metabolomics is most commonly applied to body/tissue fluids; however, recently the concept of metabolomic analysis of hair was successfully introduced by Sulek et al9 to predict foetal growthrestriction (FGR) by examination of maternal hair samples, and they found a distinct metabolite profile that distinguished FGR from normal pregnancy upon statistical comparison.…”
mentioning
confidence: 95%